KEY - الاعرجي, علي شعلان; المسعودي, منار احمد عباس (Journal of Kerbala for Agricultural Sciences, 2015)
A taxonomical key was prepared that could be used to separate the Iraqi genera of the wild bees in the family of the leaf cutting bees Megachilidae – Hymenoptera. The prepared key depended manily on the most important characters of the mouthparts of the adult males and females of the bees. The most important characters of the mouthparts were illustrated photographically. The Iraqi genera of Megachilidae included were five previously recorded in Iraqi which are (Megachile ,Chalicodoma ,Coelioxys ,Anthidium , Anthidiellum ) and two genera recorded in the present study which are (Osmia , Icteranthidium ) .